Morphological identification and molecular confirmation of the deep-sea blue and red shrimp Aristeus antennatus larvae - Marta Carreton; Joan B. Company; Laia Planella; Sandra Heras; José-Luis García-Marín; Melania Agulló; Morane Clavel-Henry; Guiomar Rotllant; Antonina dos Santos; María Inés Roldán (PeerJ, 2019)
The early life stages of the blue and red shrimp Aristeus antennatus (Decapoda: Dendrobranchiata: Penaeoidea: Aristeidae) were described by Heldt in 1955 based on plankton samples, larval rearing and assumptions of species habitat. Even with adequate keys, identification of its first larval stages remained a difficult task due to the lack of specific morphological characters which would differentiate them from other Penaeoidea species. Larvae of Aristeus antennatus were collected in the continental slope off the Spanish Mediterranean coast in August 2016 with a neuston net and preserved in ethanol 96%. DNA from the larvae was extracted and the molecular markers Cytochrome Oxidase I and 16S rDNA were sequenced and compared to that of adults with the objective of confirming the previous morphological description. Then, we present additional information to the morphological description of Aristeus antennatus larval stages through scanning electron microscopy and molecular analysis. This represents the first documented occurrence of Aristeus antennatus larvae off the Catalan coast and sets the grounds for further work on larval ecology and population connectivity of the species, which is an important contribution to a more sustainable fishery.